ANALISIS KESALAHAN PESERTA DIDIK BERDASARKAN TAHAPAN KASTOLAN DALAM MENYELESAIKAN SOAL MATEMATIKA MATERI TRIGONOMETRI KELAS XI IPA SMA NEGERI 2 PARIAMAN - RESTU YULANDA (Jurnal Edukasi dan Penelitian Matematika, 2018)
The error analysis of students is an important thing to do in order to determine the material mastery of sudents. Based on the fact, it was found that there were mistakes made by participants of XI class of SMA Negeri 2 Pariaman in solving mathematical questions of trigonometry material. The research approach is qualitative and the type of research is descriptive. Subject of this research is XI IPA class of SMA Negeri 2 Pariaman with seven students were interviewed. The data in this research are data from observations, tests, and interviews. Data were analyzed based on qualitative analysis techniques, namely data reduction, data display, and verification. Based on the results of data analysis, it was found that the student participants made mistakes include: 1) conceptual errors of 26%, that they were not able to select and apply the formula well, 2) procedural errors of 42,5%, that they incorrectly determined steps of answering questions, and 3) technical errors of 31,5%, that they incorrectly wrote and calculated the value of an arithmetic operation. Keywords—Analysis of student errors, conceptual errors, procedural errors, technical errors, trigonometry.